Interchangeability of a hepatitis A vaccine second dose: Avaxim 80 following a first dose of Vaqta 25 or Havrix 720 in children in Turkey - GÖKCE, İBRAHİM (SPRINGER, 2007)
Introduction This randomised, observer-blind clinical trial conducted in Turkey evaluated the immunogenicity, safety and interchangeability of three paediatric inactivated hepatitis A vaccines in 424 seronegative children between 1 and 15 years of age. Methods Potential subjects were screened for anti-hepatitis A virus (HAV) antibodies prior to receiving a first dose of Avaxim 80, Havrix 720 or Vaqta 25, followed by a second dose of either the same vaccine or Avaxim 6 months later. Anti-HAV antibody concentrations were measured 2 weeks after the first injection, at 24 weeks (before the second dose) and at 28 weeks for the evaluation of the immune response. Results Nearly 80% of the children between 1 and 5 years of age and half of those between the ages of 6 and 10 in the population from which the subjects were recruited were seronegative for HAV antibodies. Two weeks after the first dose, 98.2% of all subjects had anti-HAV antibody concentrations equal to or higher than 20 mIU/mL, believed to be seroprotective, and all subjects were seroprotected before and after the second dose. Anti-HAV geometric mean concentrations (GMCs) 2 weeks after the first dose and before the second were similar in children who received Avaxim and Vaqta (P=0.2), but both were higher than Havrix (P < 0.01). There were no significant differences in the anti-HAV GMCs between the study groups that received two doses of the same vaccine compared with two doses of different vaccines. There were no significant differences in the frequency of any local or systemic adverse events among the study groups following either of the two doses. Conclusion All three vaccines are safe and highly immunogenic in healthy children aged 1 to 15 years. Avaxim 80 may also be given as the second dose when Havrix 720 or Vaqta 25 are given as the first dose. The pattern of seroprevalence seen here is similar to that reported in a number of recent evaluations in Turkey, and are supportive of the routine hepatitis A vaccination of young children.
Keywords: hepatitis A vaccine; children; seroprevalence; safety; immunogenicity; interchangeability; UNIVERSAL IMMUNIZATION; VIRUS-INFECTION; IMMUNOGENICITY; SAFETY; PREVALENCE; ANTIBODIES; SEROPREVALENCE; FORMULATION; PREVENTION; ASSAYS